2006
DOI: 10.1185/030079906x80404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of twice-daily pregabalin for treating pain and related sleep interference in postherpetic neuralgia: a 13‐week, randomized trial

Abstract: Pregabalin, dosed BID, reduced neuropathic pain associated with PHN and was well tolerated. It also reduced the extent to which pain interfered with sleep. Pregabalin's effects were seen as early as week 1 and were sustained throughout the 13-week study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(130 citation statements)
references
References 21 publications
12
115
1
1
Order By: Relevance
“…This finding is in contrast to studies of postherpetic neuralgia in which BID efficacy was demonstrated across a range of doses from 150 to 600 mg/day (24). The basis for this difference in efficacy between disease states is not known, although it may be related, in part, to the permitted use of concomitant pain medication in all postherpetic neuralgia pregabalin clinical trials (24 -26).…”
Section: Safety and Tolerabilitycontrasting
confidence: 53%
“…This finding is in contrast to studies of postherpetic neuralgia in which BID efficacy was demonstrated across a range of doses from 150 to 600 mg/day (24). The basis for this difference in efficacy between disease states is not known, although it may be related, in part, to the permitted use of concomitant pain medication in all postherpetic neuralgia pregabalin clinical trials (24 -26).…”
Section: Safety and Tolerabilitycontrasting
confidence: 53%
“…The most common adverse experiences reported were generally of mild or moderate intensity and similar in frequency to those previously reported for pregabalin in studies that enrolled HIV-negative individuals. [13][14][15][16][17][18][19][20][21][22][23][24][25] Based on the primary efficacy measure, change from baseline in mean NPRS score, the current study revealed no significant difference between placebo and pregabalin treatment arms. Similarly, there were no significant differences in the secondary pain measures, including responder rates based on Ն30% and Ն50% reduction in mean weekly pain score, mBPIsf, NPSI, and GPS.…”
Section: Resultsmentioning
confidence: 99%
“…11 In one small placebo-controlled trial, gabapentin was effective in reducing pain related to HIV-DSP. 12 Pregabalin, which has an improved pharmacokinetic profile, has shown efficacy in relieving neuropathic pain associated with diabetic peripheral neuropathy, [13][14][15][16][17] postherpetic neuralgia, [18][19][20] and spinal cord injury, 21,22 and pain associated with fibromyalgia. [23][24][25] The current controlled study evaluates the efficacy and safety of pregabalin in painful HIV-DSP.…”
mentioning
confidence: 99%
“…Other published studies have confirmed these results for DPN and PHN. 87,88 In an eight-week multicenter randomized controlled study, pregabalin at 450 mg/day was found to reduce significantly the average severity of pain in patients with fibromyalgia. Other benefits included improvement in sleep quality and fatigue.…”
Section: Pregabalinmentioning
confidence: 99%